Karakterisasi Antibodi Poliklonal terhadap Aflatoksin M1 - Angriani Fusvita; Romsyah Maryam; Eko Sugeng Pribadi (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
The aim of the research was characterized the polyclonal antibody at AFM for diagnostic reagens on track 1 and measure the levels of AFM in milk. The series of experiments are given a polyclonal antibody testing 1 dimetilaminobenzidin (DAB) by dot blot immunoassay (DBIA) so it will look brown color display on the positive control sample; purification and estimation antibody of AFM concentration with ammonium sulfate; 1 dialysis; fractionation using HiTrap Protein A HP column, measured using a spectrophotometer at a wavelength of 280 nm; and characterized of IgG using SDS-PAGE. DBIA test results showed a typical reaction betweenantigen AFM1-BSA with AFM1-BSA antibody to rabbit serum in the form of brown dots after addition of DAB substrate. The results of spectrophotometric against rabbit serum fractionation showed the type of IgG heavy chain.